Case report: Ectopic production of intact parathyroid hormone (iPTH) by malignoma mimicking primary hyperparathyroidism - Wendt, Ralph; Heller, Marie; Härtwig, Daniel; Ullmann, Sven Oliver; Bisanz, Heike; Geister, Daniela; Mantovani, Luisa; Hoffmann, Ulrike (Frontiers in Oncology, 2024)
BackgroundMalignant hypercalcemia is usually caused by osteolytic processes of metastases, production of parathormone-related peptide, or secretion of 1,25-dihydroxyvitamin D. Ectopic PTH (parathyroid hormone) production by malignancy is very unusual.MethodsCase report and review of the literature.ResultsWe present a case of a malignant hypercalcemia with a presentation that mimicked primary hyperparathyroidism in a patient with endometrial carcinoma. Finally, ectopic production of PTH by a rapidly progressive neuroendocrine tumor was proven. Systematic literature review revealed ectopic PTH production by malignancies as an extremely rare cause of hypercalcemia and that most cases were initially misdiagnosed as primary hyperparathyroidism and underwent unnecessary surgical neck exploration in almost all cases.ConclusionIn patients even with a suggestive constellation of primary hyperparathyroidism, an ectopic paraneoplastic PTH source should be considered if the localization diagnostics are without abnormalities or if the PTH values are unusually high. Concomitant elevated LDH levels should also raise concern about an ectopic malignant source.